2010
DOI: 10.1111/j.1756-8765.2009.01055.x
|View full text |Cite
|
Sign up to set email alerts
|

The Education of Perception

Abstract: Although the field of perceptual learning has mostly been concerned with low-to middle-level changes to perceptual systems due to experience, we consider high-level perceptual changes that accompany learning in science and mathematics. In science, we explore the transfer of a scientific principle (competitive specialization) across superficially dissimilar pedagogical simulations. We argue that transfer occurs when students develop perceptual interpretations of an initial simulation and simply continue to use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
107
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(118 citation statements)
references
References 57 publications
10
107
0
1
Order By: Relevance
“…The ability to use basic neural machinery in novel ways may be of critical importance. As Goldstone, Landy, and Son (2010) discussed, evolutionarily speaking, we have only recently begun evaluating arithmetic expressions. Our ability to coopt perceptual machinery that has served humanity well for millennia demonstrates the remarkably efficient adaptability of the human brain.…”
Section: Arithmetic Perceptual Learning and Instructionmentioning
confidence: 99%
“…The ability to use basic neural machinery in novel ways may be of critical importance. As Goldstone, Landy, and Son (2010) discussed, evolutionarily speaking, we have only recently begun evaluating arithmetic expressions. Our ability to coopt perceptual machinery that has served humanity well for millennia demonstrates the remarkably efficient adaptability of the human brain.…”
Section: Arithmetic Perceptual Learning and Instructionmentioning
confidence: 99%
“…ey organize the changes internal to the mind that are necessary to implement learning and transfer (cf. Goldstone et al, 2010;Novick, 1990). e second theme is that learning grows in "pieces" and thinking involves using those pieces in new combinations.…”
Section: Components Of Learning To Ink and How Symbolic Languages Helpmentioning
confidence: 99%
“…Such chains of reasoning are diffi cult to do in one's head, without the external memory and perceptual processing support of symbol systems (cf. Goldstone et al, 2010). Experts are certainly capable of chains of mental reasoning without external symbolic support.…”
Section: Learning To Ink By Learning Languages To Ink Withmentioning
confidence: 99%
See 1 more Smart Citation
“…David Landy contrived an elegant experimental design which demonstrated that the colloquial notion of "manipulating symbols," such as "moving +2 across the equal sign so it becomes -2," is not just a metaphorical form of speech-in our "mind's eye" we literally move those symbols across the equal sign, so that we arrive later at our destination if the moving symbol must brave a counter current (Goldstone, Landy, & Son, 2009).…”
Section: Abstraction As Simulated Action: Learning Is Moving In New Waysmentioning
confidence: 99%